Advanced groundwater remediation active and passive technologies - Simon, F.-G; Meggyes, T.; McDonald, Chris, 1943- (Thomas Telford, 2002)
A number of techniques can be used towards containing and cleaning contaminated groundwater - either by treating or isolating the soil in situ, or by removing it for washing or disposal. Such technologies mean by high energy consumption, and can lead to new environmental problems. Therefore, more efficient and economical techniques are needed to remediate contaminated soil and groundwater.